Effect of Nitric Oxide on the Antifungal Activity of Oxidative Stress and Azoles Against Candida albicans - Li, De-Dong (Indian J Microbiol, 2016)
Nitric oxide (NO) is a small molecule with a wide range of biological activities in mammalian and bacteria. However, the role of NO in fungi, especially Candida albicans, is not clear. In this study, we confirmed the generation of endogenous NO in C. albicans, and found that the production of endogenous NO in C. albicans was associated with nitric oxide synthase pathway. Our results further indicated that the production of endogenous NO in C. albicans was reduced under oxidative stress such as menadione or H(2)O(2) treatment. Meanwhile, exogenous NO donor, sodium nitroprusside (SNP), synergized with H(2)O(2) against C. albicans. Interestingly, SNP could inhibit the antifungal effect of azoles against C. albicans in vitro, suggesting that NO might be involved in the resistance of C. albicans to antifungals. Collectively, this study demonstrated the production of endogenous NO in C. albicans, and indicated that NO may play an important role in the response of C. albicans to oxidative stress and azoles.